Synthesis of spiropyrans: H-abstractions in 3-cycloalkenyloxybenzopyrans - Gupta, Satish C.; Thakur, Mandeep; Sharma, Somesh; Berar, Urmila; Berar, Surinder; Kamboj, Ramesh C. (Beilstein Journal of Organic Chemistry, 2007)
A photochemical route for the synthesis of some benzopyronospiropyrans from 2-furyl-3-cycloalkenyloxybenzopyrones involving H-abstraction is reported. How a methyl group on the furyl ring affects the product formation is also investigated.